learning style, problem solving abilities - Rahayu Sri Waskitoningtyas (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
This study aims to determine whether or not the influence of problem solving abilities is reviewed with the learning style of mathematics education students. Data collection techniques used are questionnaires and documentation. Questionnaire method is used in learning style, while documentation method is semester test result. The sample in this research is students of mathematics semester IV and VI of Balikpapan University. Based on the results of data processing obtained conclusion there is no average difference between visual learning style, auditorial learning style, and kinesthetic learning style, so there is no effect of problem-solving abilities reviewed with the learning style of students of mathematics education University of Balikpapan. This is evident from Fobs < F0,05; 2;47 or 0.2064 < 3.1951 so that H0 is accepted. Seen from the average of learners who have kinesthetic learning style is greater than learners who have auditorial and visual learning styles.